2012
DOI: 10.1111/j.1399-5618.2011.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Early antidepressant effect of memantine during augmentation of lamotrigine inadequate response in bipolar depression: a double‐blind, randomized, placebo‐controlled trial

Abstract: This proof-of-concept study failed to show a statistically significant benefit of memantine augmentation of lamotrigine for patients with BD-D over eight weeks. However, memantine had an antidepressant effect early on in the treatment while its dose was being titrated up. Larger placebo-controlled studies are needed to ascertain optimal timing and dosing for memantine augmentation of lamotrigine in BD-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 26 publications
3
44
0
1
Order By: Relevance
“…There are insufficient data to make a recommendation regarding the use of aspirin (adjunctive) (level 3 negative),296 celecoxib (adjunctive) (level 3 negative),297 gabapentin (monotherapy) (level 3 negative),298 leviteracitam (adjunctive) (level 3 negative),299 lisdexamfetamine (adjunctive) (level 3 negative),300 memantine (adjunctive) (level 3),301 pioglitazone (adjunctive) (level 3),302, 303 riluzole (level 4 negative),304 and risperidone (adjunctive) (level 3) 305. Although adjunctive therapy with pregnenolone separated from placebo at week 6, the change in depressive symptoms was not significantly different from week 8 to week 12 between the two groups (level 2) 306…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…There are insufficient data to make a recommendation regarding the use of aspirin (adjunctive) (level 3 negative),296 celecoxib (adjunctive) (level 3 negative),297 gabapentin (monotherapy) (level 3 negative),298 leviteracitam (adjunctive) (level 3 negative),299 lisdexamfetamine (adjunctive) (level 3 negative),300 memantine (adjunctive) (level 3),301 pioglitazone (adjunctive) (level 3),302, 303 riluzole (level 4 negative),304 and risperidone (adjunctive) (level 3) 305. Although adjunctive therapy with pregnenolone separated from placebo at week 6, the change in depressive symptoms was not significantly different from week 8 to week 12 between the two groups (level 2) 306…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…Quality assessed with the Jadad scale ( Table 1; eTable 1) indicated that 4 studies Keck et al, 2009;Kelly, 2008b;Schrauwen and Ghaemi, 2006) had no quality (Jadad's scale=0), 4 (Gildengers et al, 2008;Iosifescu et al, 2009;Keck et al, 2009;Koukopoulos et al, 2012) had low quality (Jadad's scale=1), 1 (Iosifescu et al, 2009) had medium quality (Jadad's scale=2), and 5 (Ae et al, 2006;Anand et al, 2012;Ghaemi et al, 2009;Lee et al, 2014) were of high quality (Jadad's scale>3). All the studies with high quality were also RCTs, while among the studies with other designs, only 1 (Iosifescu et al, 2009) included a control group, reaching a medium quality.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…All studies focused on the short-or medium-term treatment and none reported results on relapse prevention. Nine studies were conducted in the USA (Ae et al, 2006;Anand et al, 2012;Burt et al, 1999;Ghaemi et al, 2009;Gildengers et al, 2008;Iosifescu et al, 2009;Keck et al, 2009;Kelly, 2008a;Schrauwen and Ghaemi, 2006), 2 in Asia Lee et al, 2014) and one in Europe (Koukopoulos et al, 2012). Five studies were RCTs, 2 naturalistic case series, 2 retrospective case series, 2 open label trials without a control group and 1 with a control group.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations